2016
DOI: 10.1177/0885066616682940
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphometric Neutrophil and Monocyte Markers May Strengthen the Diagnosis of Sepsis

Abstract: Background: The diagnosis of sepsis is challenging in the absence of a gold standard test. Recent studies have explored the role of neutrophil and monocyte volume, conductivity, and scatter (VCS), derived from automated hematology analyzers, in diagnosing sepsis. We assessed the diagnostic accuracy of VCS parameters in critically ill patients with sepsis. Methodology: In this prospective study, VCS parameters, procalcitonin, and C-reactive protein (CRP) were assessed in patients with proven sepsis (cases) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Their experimental results showed that MDW has a higher diagnostic performance than white cell count (WBC) in the diagnosis of sepsis. Ayres, Cornet, and Dinsdale also found that changes in the cellular complexity and nucleic acid content of neutrophils can reflect the infection status of the body, assisting the early diagnosis of sepsis (16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 97%
“…Their experimental results showed that MDW has a higher diagnostic performance than white cell count (WBC) in the diagnosis of sepsis. Ayres, Cornet, and Dinsdale also found that changes in the cellular complexity and nucleic acid content of neutrophils can reflect the infection status of the body, assisting the early diagnosis of sepsis (16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, a significant decrease in MNV and MMV values was observed after the initiation of antibiotic therapy. Similarly, Mammen et al showed that MNV and MMV were increased in patients with sepsis compared to non-septic patients admitted to ICU [126]. Noteworthy, both CPD parameters showed good diagnostic accuracy for sepsis, superior to traditional biomarkers, such as CRP and PCT.…”
Section: Mean Neutrophil Volume and Mean Monocyte Volumementioning
confidence: 92%
“…The mean neutrophil volume (MNV) and mean monocyte volume (MMV) represent the average size of the circulating neutrophil and monocyte populations, respectively. Several authors evaluated the role of MNV and MMV as biomarkers of sepsis, achieving encouraging results [124][125][126][127]. Arora et al [117] found that MNV and MMV were increased in patients with sepsis compared to controls.…”
Section: Mean Neutrophil Volume and Mean Monocyte Volumementioning
confidence: 99%
“…Mammen et al (30) probed the potential value of both neutrophil and monocyte derived CPDs; in their cohort MNV was significantly higher (P<0.001) in patients with sepsis (165.5; 95% CI, 161.6-169.4) than in nonseptic (157.3; 95% CI, 154.6-160.1) patients and donors (148.9; 95% CI, 147.9-150). A similar pattern was seen for mean monocyte volume MMV.…”
Section: Cpd In Sepsismentioning
confidence: 99%